PATH ANALYSIS TINGKAT PENGETAHUAN, SIKAP DAN PRAKTIK PETERNAK BABI TERHADAP PENGENDALIAN HOG CHOLERA DI KECAMATAN KOTA RAJA KOTA KUPANG - Toha, Larry Richard Wellem; Susetya, Heru; Nugroho, Widagdo Sri (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Pig population in East Nusa Tenggara Province in 2019 was recorded at around 2 million pigs. In east Nusa Tenggara around 85% of the households raise at least 1 (one) pig per household. Pig farming industry has its own challenges and resistances, one of the challenge is the threat of infectious diseases such as Hog cholera disease. Hog cholera is a disease caused by virus and has become endemic in most of the area in East Nusa Tenggara with relatively high prevalence. In Kupang City the prevalence of HC in 2018 was recorded at around 20,5%. The aim of this study is to analyse the relationship of pig farmer characteristics with knowledge level, attitude and practice regarding HC controlling and eradication in Kota Raja Sub-distric Kupang City. In this study, data was obtained by questionnaire and interview of pig farmers which was done in Kota Raja Sub-distric from August until October 2018. Data was analyzed with descriptive statistic and KAP studi data was analyzed with path analysis to measure the relationship between observed characteristics and HC controlling practice. The result of this study shows that variable that has the stongest relationship to practice is level of education with path coefficient (r) of -0,438 (P 0,027), followed by attitude with path coefficient (r) of 0,233 (P 0,000), and then followed by knowledge with path coefficient (r) of 0,224 (P 0,008) and the weakest realationship to practice is farmers age with path coefficient (r) of -0,049 (P 0,016).